Influence of Profitability and Debt Policy on Company Value in Health Companies - Syahbathie Sabariah; Soni Okabrian (Medikun Publisher, 2024)
This research aims to determine and test the influence of Profitability and Debt Policy both partially and simultaneously on Company Value in health sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The research population includes all health sector companies listed on the Indonesia Stock Exchange for the 2019 - 2023 period. The sample was determined using purposive sampling. The analysis techniques used in this research are descriptive analysis, classical assumption testing, and hypothesis testing using a linear regression model. The research results show that (1) Profitability has a significant effect on Company Value. This is proven by the calculated t value being greater than the t table value (5,494 > 1,667) and a significance value of (sig) (0.000 < 0.05). (2) Debt Policy does not have a significant influence on Company Value. This is shown by the calculated t value < t table, namely (0.256 < 1.667) and the significance value (sig) (0.798 > 0.05). (3) Profitability and Debt Policy simultaneously have a significant effect on Company Value. This is shown by the calculated F value > F table, namely (19.035 > 3.13) and the significance value (sig) (0.000 < 0.05). Profitability as proxied by ROI and debt policy as proxied by DAR have an influence of 34.3% on company value as proxied by PBV.